Unique neuro-ophthalmic presentation of gun pellet injury - Reena Sharma; Sanjay Sharma; Swati Phuljhele; Rohit Saxena (Oman Journal of Ophthalmology, 2016)
We describe a unique case of orbital gunshot injury with isolated intraorbital pellets lodged symmetrically in the two apices, causing identical clinical presentation, and absence of any associated globe or cerebral injury. He developed bilateral complete third nerve palsy with bilateral traumatic optic neuropathy. The optic nerve strut prevented the pellets from going into the brain on both the sides.